Administrative Control of Capital Expenditures : A Survey of Libyan Companies - العربي عبد السلام (Dirasat in Economics and Business, 1980)
The purpose of this research is to examine the control exercised by the Libyan compa- nies over capital expenditure. This control being measured in terms of the following administrative procedures: l . Capital Budget Preparations; 2. Economic Analysis of Investment; 3. Control over the Release of Funds for Approved Proposals • 4. Progress Reports; 5. Post Completion Audits. A questionaire was handed to 68 compa- nies. The response rate was 1000 0. Analysis of companies' responses (classified by type of industry, size, and average annual capital expenditures), indicates that control exer- cised by Libyan companies over funds avail- able for capital projects appears to be generally unsatisfactory.